STUDY TO DETERMINE MULTIMODAL THERAPY IMPACT ON ADRENALECTOMY FOR LOCALIZED ADRENOCORTICAL CARCINOMA AND OVERALL SURVIVAL OF PATIENTS - HUSSAIN , K; ALI , A; MEMON , AH; AHMAD , A; AHMED , B (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to determine the impact of multimodal therapy on adrenalectomy for localized adrenocortical carcinoma (ACC) and the overall survival of patients. The study included 200 patients. A retrospective analysis was conducted on 200 patients diagnosed with localized ACC who underwent adrenalectomy at a medical center. The patients were divided into the multimodal therapy group (n=100) and the adrenalectomy alone group (n=100). Patient characteristics, treatment modalities, pathological findings, and follow-up data were analyzed. The primary outcome measures included recurrence rates, overall survival rates, and treatment-related complications. The 5-year overall survival rate was significantly higher in Group B (68%) compared to Group A (45%) (p < 0.001). Group B also had a higher 5-year disease-free survival rate (54%) compared to Group A (32%) (p = 0.023). The local recurrence rate was lower in Group B (18%) compared to Group A (32%). Treatment-related adverse events occurred slightly more frequently in Group B (22%) than in Group A (15%) but did not significantly impact patient outcomes. Subgroup analyses consistently showed improved overall survival in Group B across different age groups, tumor stages, and histology. Adding multimodal therapy to adrenalectomy for localized ACC significantly improved overall survival, disease-free survival, and reduced local recurrence rates. Multimodal therapy should be considered a potential treatment approach for improving outcomes in ACC patients. Further studies with larger cohorts and prospective designs are needed to confirm these findings and optimize treatment strategies.